КУЛТУРАТА, ДРУГОСТА И ЛИТЕРАТУРАТА (Filološke studije, 2019)
This paper is primarily an overview of the past tradition in defining the very complex notion of culture. In this sense, it emphasizes the fact that the differences in defining this notion go so far as to offer contradictory definitions. Namely, many authors have different approaches in setting the semantic framework of the notion of culture. The paper cites a large number of experts who have tried to define the notion of culture and who have elaborated on aspects of intercultural communication, such as Clifford Geertz, Cvetan Todorov, Talcott Parsons, Sigmund Freud, Claude Levi-Strauss, Yuri Lotman, Edward Said, Gayatri Chakravorty Spivak, Noam Chomsky, Ivan Dzheparovski, Slavica Srbinovska and others. On this basis, we come to a general conclusion that the notion of culture is commonly associated with the following categories: a) language; b) nationality; c) ethnicity (ethnic affiliation); d) religion (religious affiliation). The main aim of the paper is to point to the theoretical research base on culture whose results can serve as literary-theoretical instruments for cultural analysis in the field of literature.